Estresse hídrico em genótipos de cajueiro do banco ativo de germoplasma da Embrapa - Pimentel, Karine Silva (2023)
The low water availability in the semi-arid Northeastern region of Brazil and the high presence of salts in the water have become a problem for the expansion of agriculture in the area, making it necessary to adopt strategies to ensure agricultural production, such as the use of saline waters. However, the concentration of salts in the water can cause significant reductions in the morphology and physiology of plants. In this context, the objective was to evaluate the effects of concentration and saline composition of irrigation water on the morphophysiology and mineral content in young dwarf cashew plants, genotype CCP 06. The experiment was conducted at Embrapa Agroindústria Tropical, located in the municipality of Fortaleza, Ceará. Treatments were arranged in a randomized block design in a 4 x 3 factorial arrangement, referring to four levels of irrigation water salinity (ECw of 0.5; 1.5; 3.0 and 4.5 dS m-1) and three types of salts used in water composition (NaCl, CaCl2 and K2SO4), with four replications and five plants per plot. The application of treatments began at 25 DAS, and evaluations were performed until 70 DAS. The increase in irrigation water salinity compromised plant growth, with reductions in dry matter production. Irrigation with K2SO4 promoted the best results in growth and dry matter production, when compared to irrigation with NaCl and CaCl2. Gas exchanges analyzed at 15 and 45 DAT responded negatively to the increase in irrigation ECw. The mineral content in leaves and roots increased with irrigation water salinity. Irrigation with NaCl provided the highest levels of Na and Cl in both leaves and roots. There was a greater translocation of Na+ from the root to the aerial part of the plants with the increase in irrigation ECw, as well as a more intensive translocation of K to the leaves. In the leaves of plants irrigated with NaCl and CaCl2, chloride ions appeared in greater quantities than the other minerals analyzed. Irrigation with CaCl2 provided the highest levels of P, Ca, and Mg in both leaves and roots. The threshold value of salinity was 2.34 dS m-1, classifying the dwarf cashew (CCP 06) as ‘moderately tolerant’ in the initial growth phase.